The Tension between Narrative Structure and Philosophical Content in Rousseau's Confessions - seyedeh Melika Sefidari; Amir nasri (حکمت و فلسفه, 2023)
In Confessions, Rousseau is looking for his representation with all its true and natural characteristics. He claims that his true and natural self can only be understood by considering the chain of his feelings, understanding the origin of these feelings and distinguishing between them in terms of being genuine or inauthentic. Rousseau leaves the conclusion about who he is to the readers in order to clear the charge of deception and self-deception. . In addition, Rousseau believes that the only valid reading is for readers to pay attention to the chain of his feelings instead of the chain of events. In this article, by using Ricoeur's analysis of the structure and design of the narrative, the narrative identity and the art of Aristotle's poetry, it is determined that the events in Confessions are configured in the form of discordant harmony and the genre of tragedy. This narrative structure imposes a form of reading on the reader that is different from Rousseau's intended reading. In the sense that based on Ricoeur's analysis of narrative identity, Rousseau's character is formed for the audience of Confessions based on the chain of narrative events and not based on the chain of Rousseau's feelings.